2020
DOI: 10.34172/jcvtr.2020.14
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of coronary artery calcium score and carotid artery intima-media thickness with severity of coronary artery disease

Abstract: Introduction : Coronary artery calcium score (CACS) and carotid artery intima-media thickness (CIMT) are the markers of atherosclerosis. An association between CACS and CIMT with presence of atherosclerotic coronary artery disease (CAD) is well established. However relationship between severity of CAD with CACS and CIMT is less clear. This study aimed to investigate the correlation between severity of CAD assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…CAC score and carotid artery intima-media thickness, can be measured as Gensini score to assess the severity of CAD [36]. It was demonstrated that short duration of sleep was associated with higher carotid artery Table 6 Crude and adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of sleep factors for Gensini score LAN, light at night; ORs, odds ratios; CIs, confidence intervals a They could read comfortably; b They could barely read; c They could see only the hazy outline of the bedroom; d Participants wore a mask to keep out light or they could not see their hand in front of their face; e Adjusted for age, sex, BMI, residence, education level, history of diabetes, hypertension and dyslipidemia, history of coronary artery disease, use of statins, antiplatelet agents, β-blockers, ACEI or ARB, smoking, drinking, diet and regular exercise; f Adjusted for age, sex, BMI, residence, education level, history of diabetes, hypertension and dyslipidemia, history of coronary artery disease, use of statins, antiplatelet agents, β-blockers, ACEI or ARB, smoking, drinking, diet and regular exercise, and adjusted mutually for other sleep factors without significant relationships with each other…”
Section: Discussionmentioning
confidence: 99%
“…CAC score and carotid artery intima-media thickness, can be measured as Gensini score to assess the severity of CAD [36]. It was demonstrated that short duration of sleep was associated with higher carotid artery Table 6 Crude and adjusted odds ratios (ORs) and 95% confidence intervals (CIs) of sleep factors for Gensini score LAN, light at night; ORs, odds ratios; CIs, confidence intervals a They could read comfortably; b They could barely read; c They could see only the hazy outline of the bedroom; d Participants wore a mask to keep out light or they could not see their hand in front of their face; e Adjusted for age, sex, BMI, residence, education level, history of diabetes, hypertension and dyslipidemia, history of coronary artery disease, use of statins, antiplatelet agents, β-blockers, ACEI or ARB, smoking, drinking, diet and regular exercise; f Adjusted for age, sex, BMI, residence, education level, history of diabetes, hypertension and dyslipidemia, history of coronary artery disease, use of statins, antiplatelet agents, β-blockers, ACEI or ARB, smoking, drinking, diet and regular exercise, and adjusted mutually for other sleep factors without significant relationships with each other…”
Section: Discussionmentioning
confidence: 99%
“…Coronary artery calci cation (CAC), quantitated by CAC score, is a hallmark in the formation and accumulation of atherosclerotic plaque [31]. CAC score and carotid artery intima-media thickness, can be measured as Gensini score to assess the severity of CAD [32]. It was demonstrated that short duration of sleep was associated with higher carotid artery intima-media thickness [33] and incidence of CAC [34].…”
Section: Discussionmentioning
confidence: 99%
“…The CACS provides a direct, noninvasive estimation of the atherosclerotic plaque burden in the coronary arteries by using either electron beam CT or multi-slice CT [28]. The CACS is one of the established surrogate markers of atherosclerosis and has an appropriate prognostic value that reflects the presence and the severity of CAD [29,30].…”
Section: Plos Onementioning
confidence: 99%